2020
DOI: 10.3390/antibiotics9120838
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drivers of Antimicrobial Use and Resistance in Poultry and Domestic Pig Farming in the Msimbazi River Basin in Tanzania

Abstract: Uncontrolled use of drugs both in humans and animals coupled with environmental contamination exacerbate the development and spread of antimicrobial resistance. This paper assessed the drivers of antimicrobial use and resistance in poultry and domestic pig farming and the environment. Questionnaires, in-depth interviews, and focus group discussions (FGDs) were used to collect information regarding demographic characteristics, knowledge, practices, attitudes, and perceptions of the drivers of antimicrobial use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 39 publications
6
51
0
Order By: Relevance
“…However, lack of information regarding how much is allocated to AMR-specific research is an indication of a lack of clear strategies to achieve the identified AMR objectives and goals. Moreover, in reviewing AMR articles (published from 2018–2020) none has indicated receiving financial assistance from the government of Tanzania [ 6 , 12 , 13 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, lack of information regarding how much is allocated to AMR-specific research is an indication of a lack of clear strategies to achieve the identified AMR objectives and goals. Moreover, in reviewing AMR articles (published from 2018–2020) none has indicated receiving financial assistance from the government of Tanzania [ 6 , 12 , 13 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed literature demonstrates contrary findings about AMR education and public awareness in most African countries. Notably, there is little continuing education on AMU for key stakeholders such as prescribers and livestock keepers, including poultry farmers [ 6 ]. In many cases, irrational prescription practices are also driven by subtle violation of medical ethics at the expense of economic and professional profiteering [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transmission of resistant bacteria between animals and humans has also been reported in many studies [ 30 , 31 , 32 ]. For example, a report on antimicrobial use and resistance in Africa indicated a 100% prevalence of MDR E. coli in South Africa with isolates highly resistant to sulphonamides, tetracycline, and penicillin [ 33 ]. The high percentage of resistance to these antibiotics may be because they are widely used, favoured by their low cost and availability [ 32 ].…”
Section: Discussionmentioning
confidence: 99%